The ABCs of fiber optic communication - Warier, Sudhir (Artech House applied photonics series., 2017)
Includes the latest technological advancements and industry applications, this unique practical book provides the conceptual framework and troubleshooting tactics related to the manufacturing, selection, and installation of modern photonic networks. --